The Role of Financial Literacy, Income Level, and Lifestyle in Shaping Financial Management of Millennial Employees in Denpasar City - Sudarmini, Ketut; Sariani, Ni Ketut; Ganawati, Nengah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examined the influence of financial literacy, income level, and lifestyle on the financial management practices of millennial employees in Denpasar City. Financial management referred to the efficient handling of finances, while financial control involved evaluating whether financial management aligned with the budgeted plans. Millennial employees faced challenges such as limited financial resources and rising living costs, highlighting the need for strong personal financial management skills. The study aimed to address issues like impulsive spending and poor financial planning among millennials. Data were gathered from 75 respondents through a validated and reliable Likert scale questionnaire, selected via incidental sampling. Descriptive analysis provided a profile of the respondents, which served as a foundation for further statistical analysis using multiple linear regression.